1994
DOI: 10.1038/370567a0
|View full text |Cite
|
Sign up to set email alerts
|

A conserved retinoic acid response element required for early expression of the homeobox gene Hoxb-1

Abstract: Within the Hoxb homeobox gene complex, Hoxb-1 is the earliest member expressed in the mesoderm and neuroectoderm of primitive streak and presomite embryos, preceding rhombomere-restricted expression in the hindbrain. Ectopic exposure of embryos to retinoic acid alters spatial aspects of Hox gene expression patterns. However, the role of retinoids in regulating these genes during normal development is unclear. We have now identified two enhancers, 3' of the mouse Hoxb-1 gene, which together reconstruct the earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
260
1
1

Year Published

1996
1996
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 431 publications
(266 citation statements)
references
References 30 publications
4
260
1
1
Order By: Relevance
“…These characteristics led to the original proposal to sequence the Fugu genome in order to assist with the annotation of human genes based on comparative genomics [10]. Furthermore, the availability of Fugu genomic sequence also revealed that human-Fugu conserved noncoding sequences can be used to delineate gene regulatory sequences [1,[11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…These characteristics led to the original proposal to sequence the Fugu genome in order to assist with the annotation of human genes based on comparative genomics [10]. Furthermore, the availability of Fugu genomic sequence also revealed that human-Fugu conserved noncoding sequences can be used to delineate gene regulatory sequences [1,[11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The Role of RA Receptors and Prep1 in Actin-dependent HoxB Induction by RA Because RARs are important in HoxB expression in the neural region (Marshall et al, 1994(Marshall et al, , 1996Gould et al, 1998), we tested whether treatment with CytD affected the expression of any of these receptors. As shown in Table 3, CytD did not affect the expression levels of any of the RAR and retinoid X receptor (RXR) transcription factors, either in the absence or in the presence of RA.…”
Section: N-wasp Down-regulation Inhibits the Expression Of The Hoxb Cmentioning
confidence: 99%
“…Cell fate-determining clustered Hox genes are expressed colinearly in the same order as their location on the genome, generating anteriorto-posterior identities (Krumlauf, 1994). Several lines of evidence have demonstrated the importance of RA receptors (RARs) for patterning and basal expression of Hox genes in the vertebrate neural tube (Marshall et al, 1994(Marshall et al, , 1996Gould et al, 1998;Dupe et al, 1999). However, expression of anterior HoxB genes also depends on an auto-regulatory circuit involving the HoxB1 protein and the Prep1-Pbx1 complex (Marshall et al, 1996;Maconochie et al, 1997;Dupe et al, 1999;Jacobs et al, 1999;Ryoo et al, 1999;Ferretti et al, 2000Ferretti et al, , 2005Huang et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…RA directly regulates gene expression through its nuclear hormone receptor (RAR) and co-receptor (RXR), which bind RA response elements (RAREs) in the enhancers of target genes (Bastien and Rochette-Egly, 2004). In the hindbrain, RA regulates the expression of 3Ј-Hox genes through direct (in the case of Hox-1 and Hox-4 genes) or indirect (in the case of Hox-3 genes) mechanisms (Gould et al, 1998;Hernandez et al, 2004;Marshall et al, 1994;Nolte et al, 2003;Studer et al, 1994;Zhang et al, 2000). Other anterior RAresponsive genes (Hox-1 family genes) are expressed earlier and at lower RA concentrations than the more-posterior RA-responsive genes (Hox-4 family genes) (Dupe and Lumsden, 2001;Maves and Kimmel, 2005;Simeone et al, 1990).…”
Section: Introductionmentioning
confidence: 99%